Efeito da temperatura no desenvolvimento de imaturos de Paralucilia fulvinota (Bigot, 1877) (Diptera: Calliphoridae) de interesse forense - Sales, Tohnson (Instituto Nacional de Pesquisas da Amazônia - INPA, 2015)
Forensic entomology uses information based on the biology of some insects, mainly Diptera Calliphoridae, which are associated to corpses in forensic investigations. Temperature has direct effect on the metabolism rate. Higher temperatures reduce the development time and has a direct effect on the body mass and length. This research aims at studying the effects of ambient temperature (average temp. =24,5 ± 1,3ºC; average humidity 84 ± 3,9%), in 5 different rates of controlled temperature (20, 23, 26, 29, 32 and 35 ºC), on the development of P. fulvinota, thus generating data to help estimate the PMI (Postmortem Interval) of 5 corpses found in this area. The research was conducted at Reserva Florestal Ducke (Manaus-Amazonas). Five pregnant female mosquitoes were collected when feeding upon a forty-kilo swine (Sus scrofa). After being laid, immatures were collected from stock colonies. In ambient temperature, the individuals development took 13 days. Gender ratio was 0,86 (7 ♂ and 46 ♀). There was a constant mass gain through each instar phase in relation to the larvae length. The data in degree day (190.38) and degree hour (4569.24) of the total development time from larvae (L1, L2, L3) to adult reveal the elapsed time to reach the total period. Development time under controlled temperature was longer in 20º C (~25 days) with a gender ratio of 0,3 (7 ♂ and 3 ♀), whereas the shorter was in 29º C (~11 days). Gender ratio: 0,6 (18 ♂ and 27 ♀). At 23º C, 19 days, gender ratio: 0,45 (13 ♂ e 11 ♀) and 26º C, 13 days, gender ratio: 0, 5 (21 ♂ e 21 ♀). At 23º and 26º C there was a consistent length growth, unlikely the other temperatures where the growth rate was decreased. Regarding body mass there was gain in all temperatures apart from 29º C. At 32º and 35º C incomplete development occurred. Under controlled temperatures the optimal temperatures ranged between 23 and 26º C and in fluctuating temperatures, average 24, 5º C. In order to obtain an accurate result using PMI calculation, results from experiments under controlled and ambient temperatures were used and complemented each other, confirming the temperature influence on the development time, body mass and length. This study represents an important tool to forensic entomology and the PMI estimation in corpses found in this region.
Keywords: Paralucilia fulvinota; Entomologia forense; Decomposição